2020
DOI: 10.3390/healthcare8030347
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Mental and Physical Functions Affect Subjective Cognitive Decline in Community-Dwelling Elderly Japanese People

Abstract: Subjective cognitive decline (SCD) is complex and not well understood, especially among Japanese people. In the present study, we aimed to elucidate the relationships of subjective and objective mental and physical function with SCD among older community-dwelling Japanese adults. SCD was evaluated using the Kihon Checklist: Cognitive Function. Other parameters were evaluated using the Mini-Mental State Examination (MMSE) and the five-item version of the Geriatric Depression Scale (GDS-5), for an objective ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
(103 reference statements)
1
6
2
Order By: Relevance
“…Our finding that PDS predicted SM difficulties is consistent with a large body of research (Goda et al, 2020; Künzi et al, 2021; Potter et al, 2009; Rönnlund et al, 2011; Sabatini et al, 2021). Since there is a link between chronic stress and PDS conditions, such as depression (Monroe & Harkness, 2005), it has been proposed that long-term PDS may damage the neurogenesis in the hippocampus, a brain region crucial for supporting memory (Dillon & Pizzagalli, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that PDS predicted SM difficulties is consistent with a large body of research (Goda et al, 2020; Künzi et al, 2021; Potter et al, 2009; Rönnlund et al, 2011; Sabatini et al, 2021). Since there is a link between chronic stress and PDS conditions, such as depression (Monroe & Harkness, 2005), it has been proposed that long-term PDS may damage the neurogenesis in the hippocampus, a brain region crucial for supporting memory (Dillon & Pizzagalli, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…However, the MMSE score was not associated with SCD risk according to our logistic regression analysis. A previous study [ 37 ] has similarly reported that MMSE scores are not associated with the development of SCD in community-dwelling older adults. This is probably because the MMSE score did not fully capture the early stage of cognitive decline observed in SCD.…”
Section: Discussionmentioning
confidence: 97%
“…SCD morbidity (i.e., KCL-CF score ≥ 1) was found in 35.3% of our study population. This rate has been variously estimated in prior research on community-dwelling older adults at 32.5% [ 28 ], 34.5% [ 36 ], 34.9% [ 29 ], 35.4% [ 37 ], and 37.6% [ 38 ]. Moreover, high response rate to options that suggest SCD was recorded for the following questions: “Do your family or your friends point out your memory loss?” and “Do you find yourself not knowing today’s date?”.…”
Section: Discussionmentioning
confidence: 99%
“…The MMSE is internationally popular as a screening test for dementia and is characterized by task contents like writing, sentence construction, and graphical imitation. The maximum score is 30 points, and a person is suspected to have dementia if they obtained a score of 23 points or less [ 34 ].…”
Section: Methodsmentioning
confidence: 99%